Adoption of mobile money among internal migrant workers during the corona pandemic in India: a study focused on moderation by mode of payments. (31st March 2022) - Prakash, Anand; Mahajan, Yogesh; Gadekar, Ashutosh
The paper studies the impact of the corona pandemic on the adoption and diffusion of mobile payments (m-payments) among internal migrant workers in India. These internal migrant workers in India constitute approximately one-third of the workforce. Protection motivation theory (PMT) and unified theory of acceptance and use of technology (UTAUT) are models used to examine the impact of the corona pandemic on the adoption of m-payments systems among internal migrant workers in India. A schedule was filled by 400 such migrant workers in India during the pandemic period. The data were analysed using structural equation modelling (SEM). Analysis shows that social influence, effort expectancy, facilitating conditions, perceived severity, self-efficacy, and response efficacy during the corona pandemic significantly influence the migrant workers' behavioural intention. The mode of payment convenience acts as a moderator between response efficacy and behavioural intention.